قصص الأنبياء بين كتابي سرائر أسرار النطقاء وفصوص الحكم (دراسة مقارنة): Stories of the Prophets Between the Books Sarāʾir Asrār Al-Nuṭaqāʾ and Fuṣūṣ Al-Ḥikam (a Comparative Study) - Faiz Mursyid Lidinillah; Hassan Abul Mukarram; Abdullah Ahmed Albatli (البصيرة: مجلة الدراسات الإسلامية, 2026)
This study presents a comparative analysis of the stories of the prophets as found in Sarāʾir Asrār al-Nuṭaqāʾ by Jaʿfar b. Manṣūr al-Yaman and Fuṣūṣ al-Ḥikam by Muḥyī al-Dīn Ibn ʿArabī. It focuses on examining the interpretive approaches employed by both authors, particularly their use of allegorical and esoteric interpretations in understanding prophetic narratives. The research aims to identify how these narratives are utilized to support their theological perspectives, as well as to highlight the similarities and differences between them in both methodology and conclusions. The story of Prophet Noah (peace be upon him) is selected as a case study due to its central significance in the Qur’an and the distinctive interpretations presented by both authors, which often diverge from the apparent meanings of the scriptural texts. This study adopts a comparative analytical method by examining relevant passages from both works and analyzing them in light of the understanding of Ahl al-Sunnah wa al-Jamāʿah. The findings reveal that both works rely on esoteric interpretation; however, Jaʿfar al-Yaman employs it to support the doctrine of Imamate in Ismaili thought, whereas Ibn ʿArabī uses it to establish philosophical Sufi concepts, particularly the doctrine of the Unity of Being, leading to interpretations that depart from orthodox textual understanding.